Surface electromyography using textile-based electrodes - Catarino, André P. (2012)
Surface Electromyography (sEMG) is a fundamental method for study the biomechanical behavior of a person, allowing the extraction of valuable information for health professionals. This paper presents a research conducted with the purpose of developing textile electrodes for noninvasive surface electromyography. Conducting fibers were used in a specifc arrangement taking into consideration SENIAM recommendations and embedded in a textile fabric. A comparison was made between conventional electrodes and the proposed ones. The results showed that the behavior is similar, which can constitute a valid alternative, overcoming some disadvantages such as the comfort for the user.